2022
DOI: 10.1128/aem.01964-21
|View full text |Cite
|
Sign up to set email alerts
|

A Superefficient Ochratoxin A Hydrolase with Promising Potential for Industrial Applications

Abstract: As the most seriously controlled mycotoxin produced by Aspergillus spp. and Penicillium spp., ochratoxin A (OTA) results in various toxicological effects and widely contaminates agro-products. Biological detoxification of OTA is the most priority in food and feed industry, but currently available detoxification enzymes are relatively low effectiveness in time and cost. Here we show a superefficient enzyme ADH3 identified from Stenotrophomonas acidamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 54 publications
1
48
2
Order By: Relevance
“…Open reading frames (ORFs) of two genes that encode enzymes NA and ADH3 were amplified from the CW117 genome, ligated to vector pGEX-4T-1, and transferred into E. coli BL21 for protein expression. Gene adh3 has been fully characterized in Luo et al ( 11 ), the repeated ADH3 results were not shown (or only as a parallel comparison) in this study. As shown in Fig.…”
Section: Resultscontrasting
confidence: 59%
See 4 more Smart Citations
“…Open reading frames (ORFs) of two genes that encode enzymes NA and ADH3 were amplified from the CW117 genome, ligated to vector pGEX-4T-1, and transferred into E. coli BL21 for protein expression. Gene adh3 has been fully characterized in Luo et al ( 11 ), the repeated ADH3 results were not shown (or only as a parallel comparison) in this study. As shown in Fig.…”
Section: Resultscontrasting
confidence: 59%
“…As described in a previous publication, 53 hydrolase genes, which may potentially be used for OTA detoxification, were selected for degradation testing from the CW117 genome (GenBank accession no. CP062156.1 ) ( 11 ). Two genes, adh3 (protein, ADH3) and na (protein, NA), were screened and characterized for OTA degradation activity by heterologous protein expression in Escherichia coli BL21 and enzymatic degradation test in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations